Application of Audio Visual Media to Increase Interest in Learning Indonesian Language Content for Class IV Students at Nurul Anwar Elementary School - Auliaulfattah, Farah; Ramadianti, Fatimatus Izzati; Roziah (Journal of Action Research in Education, 2025)
This research explores how the use of audio-visual media can increase the learning interest of grade IV students at SD Nurul Anwar, especially in learning Indonesian. Using a qualitative approach and descriptive methods, this research involved 15 students. In this research the teacher used the inquiry learning model and the lecture learning method. The results show that the use of audio-visual media significantly influences students interest in learning compared to conventional learning methods. The implication is the need for educators to integrate audio-visual media in learning to increase students interest in learning.